A geometrical model for void saturation in air-entrained concrete under continuous water exposure. (15th October 2016) - Liu, Zhichao; Hansen, Will
Highlights: The presence of over-pressure in concrete pores/voids account for the moisture transport characteristics. A geometrical model for gradual saturation of air void proposed, based on which service life is predicted. Air void characteristics are simulated using an S-shaped curve and the effect is investigated by the geometrical model. Abstract: Moisture transport properties in concrete have been shown to have great implications on the freeze-thaw (F-T) durability. In this paper, the slow process of gradual air void filling in air-entrained concrete under continuous wet exposure is further explored based on Fagerlund's work. The concomitant effect on the air-void properties is quantified by a geometrical model, where the change in specific surface and void spacing is computed due to gradual void saturation of different size classes based on the linear traverse method. This information, when combined with the measured secondary rate of water absorption, is able to predict the time to reach a critical saturation level gauged by the threshold void spacing, as exemplified by an air-entrained 0.45 water-cement (w/c) ratio concrete mix. Air void characteristics (air content and the size distribution), the important factors in controlling internal frost durability, are simulated using an S-shaped curve and their effect on the critical time is investigated by this geometrical model.